Síntese de 4-organocalcogenil-1h-isocromen-1-iminas e 3-(alquil calcogenoil-2-benzofenil[b]selenofeno[2,3-d] calcogenofenos via reações de ciclização mediadas por sais de ferro - Santos Neto, José Sebastião dos (2016)
In this work we developed the efficient and selective heterocyclic product synthesis using as electrophilic agent a ferric chloride combinated with diorganyl dichalcogenides under mild conditions. In the first part of this work, it was possible a variety of 4-organochalcogenyl-1H-isochromen-1-imines synthesis using a combinated system of diorganyl dichalcogenides and anhydrous ferric chloride using o-alkynylbenzamides as a substrate. These product synhesis given high efficiently and selectivity in 35 for 88% yields. These synthetized products were submeted to palladium coupling reactions leading to expected products in 65 for 80% yields. In a second stage, it was possible a 3-(alkyl chalcogen-2- benzophenyl[b]selenophene[2,3-d] chalcogenophenes using a combinated system with dialkyl diorganyl dichalcogenides and hexahidrate ferric chloride. Through this cyclization protocol we could satisfactorily synthetize a series of benzochalcogenophenes chalcohenofene-fused (35 to 89% yields), using relatively mild reaction condictions, since all the experiments were carried at 39°C under ambient atmosphere.